Manajemen Mutu Pendidik Pondok Pesantren Ar-Rohmah Putri Malang - Rosyada, Amrina; Handayani, Khalifaturrosyidah; Munazzalurrohmi, M.; Fikri, Shofil (Universitas Pakuan, 2025)
QUALITY MANAGEMENT OF EDUCATORS AT AR-ROHMAH PUTRI ISLAMIC BOARDING SCHOOL MALANGThis study aims to analyze the quality management of educators at Ar-Rohmah Putri Islamic Boarding School Malang based on the perspective of Human Resource Management theory and analyze the challenges and expectations in the quality management of educators at Ar-Rohmah Putri Islamic Boarding School Malang. A qualitative and case study approach was used to explore the implementation of recruitment and selection, training and development, performance appraisal, and leadership and motivation in improving the quality of educators. The results showed that the boarding school implements a strict recruitment and selection process with specific criteria, holistic training that includes academic and spiritual aspects, performance assessment based on Key Performance Indicators (KPI), as well as supportive leadership and motivational strategies such as scholarships to encourage educators' professionalism. Challenges faced include character differences, competency development, and limited access to technology. However, adaptive and collaborative efforts are made to overcome them. The pesantren's hope is to produce international standard educators with global insights and commitment to Islamic values, through development programs such as sanad retrieval and international daurah. These findings confirm the importance of effective human resource management in maintaining and improving the quality of education in the pesantren environment, especially in modern islamic boarding school.